Nanostructured Ni2P as a Robust Catalyst for the Hydrolytic Dehydrogenation of Ammonia–Borane. Issue 52 (6th November 2015) - Peng, Cheng‐Yun; Kang, Lei; Cao, Shuang; Chen, Yong; Lin, Zhe‐Shuai; Fu, Wen‐Fu
Abstract: Ammonia–borane (AB) is a promising chemical hydrogen‐storage material. However, the development of real‐time, efficient, controllable, and safe methods for hydrogen release under mild conditions is a challenge in the large‐scale use of hydrogen as a long‐term solution for future energy security. A new class of low‐cost catalytic system is presented that uses nanostructured Ni2 P as catalyst, which exhibits excellent catalytic activity and high sustainability toward hydrolysis of ammonia–borane with the initial turnover frequency of 40.4 mol(H2) mol(Ni2P) −1 min −1 under air atmosphere and at ambient temperature. This value is higher than those reported for noble‐metal‐free catalysts, and the obtained Arrhenius activation energy ( E a =44.6 kJ mol −1 ) for the hydrolysis reaction is comparable to Ru‐based bimetallic catalysts. A clearly mechanistic analysis of the hydrolytic reaction of AB based on experimental results and a density functional theory calculation is presented. Abstract : A low‐cost catalytic system using nanostructured Ni2 P as the catalyst was established for the hydrolysis of ammonia–borane. This system exhibits excellent catalytic activity and high sustainability under an air atmosphere and at ambient temperature.